Traffickers’ Use of Substances to Recruit and Control Victims of Domestic Trafficking for Sexual Exploitation in the American Midwest - Koegler, Erica; Wood, Claire; Bahlinger, Lilly; Johnson, Sharon (Anti-Trafficking Review, 2022)
This paper describes how traffickers use substances to recruit and control victims of domestic trafficking for sexual exploitation, as reported by service providers working with trafficking survivors in the American Midwest. This data was derived from interviews with 15 service providers in a major metropolitan area. Findings revealed consistencies with previous literature and new insights into the trafficker- substance use dynamic. Traffickers’ use of substances with victims was pervasive when trafficking was for the purpose of sex but not other labour. There were several examples of how traffickers use substances for victim exploitation and recruitment. These include using substances to ensure a victim is in a euphoric mood prior to sex work, to reward victim sex work productivity, and to initiate withdrawal effects to demonstrate the traffickers’ supreme control. Novel findings include how and why traffickers might deny victim use of substances and how they might give substances to victims without the victim’s knowledge. Implications for how these findings can be utilised for victim treatment and for future research are discussed.